Baseline-dependent sampling and windowing for radio interferometry: data compression, field-of-interest shaping, and outer field suppression. Issue 4 (14th March 2018) - Atemkeng, M; Smirnov, O; Tasse, C; Foster, G; Keimpema, A; Paragi, Z; Jonas, J
Abstract: Traditional radio interferometric correlators produce regular-gridded samples of the true uv -distribution by averaging the signal over constant, discrete time–frequency intervals. This regular sampling and averaging then translate to be irregular-gridded samples in the uv -space, and results in a baseline-length-dependent loss of amplitude and phase coherence, which is dependent on the distance from the image phase centre. The effect is often referred to as 'decorrelation' in the uv -space, which is equivalent in the source domain to 'smearing'. This work discusses and implements a regular-gridded sampling scheme in the uv -space (baseline-dependent sampling) and windowing that allow for data compression, field-of-interest shaping, and source suppression. The baseline-dependent sampling requires irregular-gridded sampling in the time–frequency space, i.e. the time–frequency interval becomes baseline dependent. Analytic models and simulations are used to show that decorrelation remains constant across all the baselines when applying baseline-dependent sampling and windowing. Simulations using MeerKAT telescope and the European Very Long Baseline Interferometry Network show that both data compression, field-of-interest shaping, and outer field-of-interest suppression are achieved.